Kampus dan Republik: Merawat Republik, Mengaktifkan Akal Sehat? - Siti Nurhayati; Masduki Asbari; Umul Musfiroh (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to determine the function of campuses and republican ideas. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to an oral narrative from the Bosowa University YouTube channel entitled